2023
DOI: 10.3389/fmicb.2023.1145315
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and analytical validation of a metagenomic reference catalog of human gut microbiota based on co-barcoding sequencing

Abstract: Human gut microbiota is associated with human health and disease, and is known to have the second-largest genome in the human body. The microbiota genome is important for their functions and metabolites; however, accurate genomic access to the microbiota of the human gut is hindered due to the difficulty of cultivating and the shortcomings of sequencing technology. Therefore, we applied the stLFR library construction method to assemble the microbiota genomes and demonstrated that assembly property outperformed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Previous studies have amply demonstrated the huge potential of linked reads in metagenomic studies [ 3 , 8 , 9 , 11 ]. Here, we evaluated the performance of linked reads in detecting taxonomic abundance and genomic variants using LRTK.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have amply demonstrated the huge potential of linked reads in metagenomic studies [ 3 , 8 , 9 , 11 ]. Here, we evaluated the performance of linked reads in detecting taxonomic abundance and genomic variants using LRTK.…”
Section: Resultsmentioning
confidence: 99%
“…The hidden long-range information they provide enables local assembly of co-barcoded reads and thus significantly increases the number of high-quality metagenome-assembled genomes (MAGs) [ 8 ]. In longitudinal sequencing datasets [ 3 , 9 , 10 ], the barcodes associated with linked reads promote the phasing of genomic variants and refine the identification of intrahost evolution of gut microbiota. In some complex environments, such as soil, linked-read sequencing has been shown to aid in the investigation of the involved microbial genomes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%